PENGARUH PRESTASI KERJA DAN SENIORITAS TERHADAP PROMOSI JABATAN PADA HOTEL HARRIS DI TUBAN - Yuyun Dian Ningrum (Majalah Ilmiah Widyacakra, 2019)
The purpose of this study is to determine the effect of work performance and seniority on promotion of position at Hotel HarisTuban. The sample of this research is 90 respondents at Hotel Harris Tuban. Sources of data used are primary and secondary data. Data analyzed by using computer program SPSS for Windows ver 22. Data collection method in this research use interview technique, questionnaire, documentation and observasi.Teknik data analysis using assumption test of classical, multiple correlation, multiple linear regression, determination, f test and test t. The results of this study indicate that job performance and seniority have significant influence simultaneously and partially on the promotion of position, it is proved from the result of f-test obtained F-count as big as 142,662 bigger than Ftabel is 3.11 this means there is significant influence together (simultaneously) from work performance and seniority at Hotel Harris Tuban. While on t test the t-value of the independent variables consist of performance and seniority performance, respectively, among others 9,193 and 6,432 which is bigger than t-table of 2.000 this means there is partially significant influence between work performance and seniority toward promotion Hotel Harris Tuban.